Risk factors for parastomal hernia after abdominoperineal resection of rectal cancer - Zhu, Lele; Li, Shun; Wang, Feitong (Frontiers in Oncology, 2024)
PurposeTo investigate risk factors associated with the formation of parastomal hernia after Miles operation, and to provide scientific evidence for the prevention and treatment of parastomal hernia.MethodsClinical data from 205 patients with rectal cancer undergoing Miles operation in the Department of General Surgery, Affiliated Hospital of Xuzhou Medical University between May 2016 and May 2021 were analyzed retrospectively. Fourteen potential factors were selected and analyzed by single factor analysis and two element logistic regression analysis for their potential relationship to incidence of parastomal hernia.Results49 cases of parastomal hernia occurred among 194 patients during follow-up (incidence 25.26%). Univariate analysis showed that age, thickness of subcutaneous abdominal fat, BMI, and stoma pathway were related to the formation of post-surgical parastomal hernia (P < 0.05). Two element logistic regression analysis showed that advanced age, thickness of subcutaneous abdominal fat, BMI > 25 kg/m2, and transperitoneal surgical approach were independent risk factors for the formation of parastomal hernia after Miles operation (P < 0.05).ConclusionAdvanced age, thickness of subcutaneous abdominal fat, BMI > 25 kg/m2, and transperitoneal surgical approach are independent risk factors for the formation of parastomal hernia after Miles.